2003
DOI: 10.3732/ajb.90.8.1159
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal biology of Liatris scariosa var. novae‐angliae (Asteraceae), a rare New England grassland perennial

Abstract: Propagule dispersal biology is a crucial avenue of research for rare plant species, especially those adapted to disturbance, such as northern blazing star (Liatris scariosa var. novae-angliae), a rare, early-successional New England grassland perennial. We examined the dispersal ability of northern blazing star propagules collected from 14 populations covering the entire latitudinal range of the taxon. Multiple regression demonstrated that dispersal ability, as measured by drop time in still air and flight dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 37 publications
4
41
1
Order By: Relevance
“…The similar impact of irradiance level on mass of seeds was observed in Helianthus annus (Santalla et al 2002). Moreover, the differentiation of achene dimensions and mass in various site conditions was found in several taxa from Asteraceae family (Washitani & Nishiyama 1992;Meyer 1997;Meyer & Carlson 2001;Gravuer et al 2003;Riba et al 2005;Fumanal et al 2007). Regardless of substantial differences of size of Bidens frondosa seeds among consecutive sites and years the recruitment values did not showed the spatial and temporal variability.…”
Section: Bidens Frondosasupporting
confidence: 51%
“…The similar impact of irradiance level on mass of seeds was observed in Helianthus annus (Santalla et al 2002). Moreover, the differentiation of achene dimensions and mass in various site conditions was found in several taxa from Asteraceae family (Washitani & Nishiyama 1992;Meyer 1997;Meyer & Carlson 2001;Gravuer et al 2003;Riba et al 2005;Fumanal et al 2007). Regardless of substantial differences of size of Bidens frondosa seeds among consecutive sites and years the recruitment values did not showed the spatial and temporal variability.…”
Section: Bidens Frondosasupporting
confidence: 51%
“…One hundred perigynia and achenes were released individually from the top of the tube, and the time required for them to fall from the release point to the bottom of the tube was measured with a digital stopwatch. Fall rate (cm s -1 ) was calculated over this height (Gravuer et al, 2003). (c) 100 perigynium and achenes, which were parallel to the flat perigynium/achene-landing surface, were exposed for 60 s to a constant stream of air produced by an electric fan.…”
Section: Dispersal Characteristicsmentioning
confidence: 99%
“…In order to reduce the number of statistical tests, we performed these analyses only on the two traits thought to best reflect dispersal ability, pappus length and PSpeed, as well as on the first axis of the principal component analysis (Factor1). Pappus length was chosen because Gravuer et al (2003) found that this trait alone was significantly related to flight distance but not to drop time (inversely related to terminal velocity) in Liatris scarios, another Asteraceae.…”
Section: Diaspore Traitsmentioning
confidence: 99%
“…Wing load ratio was calculated as the ratio of average diaspore weight over average pappus total projected area (p(PW/2)(PW/2 + Ö(PL 2 +(PW/ 2) 2 )). Wing load ratio was square root transformed (RLWR) as in Gravuer et al (2003). Because the various traits were correlated, and in order to limit the number of comparisons among populations, we performed a principal component analysis on each original data set using the basic measurements (AL, PL, AW, PW and DW) (Proc FACTOR of SAS, 1999).…”
Section: Diaspore Traitsmentioning
confidence: 99%